Implementasi Rezim Internasional dalam Menangani Conflict-Related Sexual Violence di Tigray - Venisa Yunita Sari; Nurfitri Nugrahaningsih; Ully Nuzulian (Intermestic: Journal of International Studies, 2022)
This study aims to analyze the effectiveness of the international regime implementation in using conflict-related sexual violence as a strategy in the armed forces conflict in Tigray. This study uses descriptive qualitative research methods by taking sources from books, journals, online articles, and internet sites through literature studies. Based on Arild Underdal's theory of the effectiveness of the international regime with the concept of human security, it was found that the international regime was ineffective in dealing with conflict-related sexual violence against women in Tigray. Based on an analysis of three variables, such as dependent variable, independent variable, and intervening variable which indicates that the member countries are not complying with the rules of the related international regime, so that the operationalization of the regime in the mission is not optimal, and has an impact on the failure of the current target set.